Sulfonamide supported catalysts for the ring opening polymerisation of cyclic esters - Schwarz, A (2010)
This Thesis describes the synthesis and characterisation of sulfonamide supported titanium, zirconium and aluminium complexes and their use as ring opening polymerisation catalysts for ε-caprolactone and rac-lactide. Chapter 1 introduces polyester use, development and characterisation in general. Metal catalysed ring opening polymerisation of cyclic esters is considered in a literature review of the field. Titanium, zirconium and aluminium complexes supported by polydentate sulfonamide ligands are also discussed. Chapter 2 describes the synthesis and characterisation of new sulfonamide supported titanium amide, isopropoxide and zirconium isopropoxide complexes. Their application as catalysts for the ring opening polymerisation of ε-caprolactone and rac-lactide is discussed and compared with known zirconium isopropoxide complexes supported by bis(phenolate) amine ligands. Chapter 3 describes the synthesis and characterisation of Cs symmetric titanium amide and alkoxide complexes supported by dianionic, tri- and tetradentate sulfonamide ligands. Zirconium alkyl and amide complexes supported by C3- symmetric trianionic ‘tren’ type ligands bearing three different sulfonamide groups are also presented. The application of these complexes for the ring opening polymerisation of ε-caprolactone and rac-lactide is described and compared with the complexes presented in Chapter 2. Chapter 4 provides an overview of the synthesis and characterisation of aluminium alkoxide and alkyl complexes supported by dianionic, tri- and tetradentate sulfonamide ligands. Solution state behaviour and solid state structures are presented and discussed. An assessment of these complexes for the ring opening polymerisation of rac-lactide is presented. Chapter 5 presents full experimental procedures and characterisation data for the new complexes reported. CD Appendix contains .cif files for all new crystallographically characterised complexes described, and additional polymerisation graphs.